A comparison study of smartphone acceptance between Korea and the USA. (2015) - Jung, Chang Mo; Hur, Won-Moo; Kim, Yeonshin
This research empirically tested cultural differences in the relationship between the components of unified theory of acceptance and use of technology (UTAUT) and trust. Using an online survey to collect data from mobile phone service users in Korea and the USA, we found two meaningful outcomes that may improve the understanding of technology acceptance behaviour. First, trust in smartphones significantly increased usage intentions, whereas trust formation was affected by users' expectancy of both performance and effort. Second, the relationship between the proposed UTAUT model constructs differed between the two countries. These findings indicate that trust in technological artefacts plays an important role in explaining technology adoption, and that culture may moderate the extent to which the antecedents of the technology acceptance model affect trust and usage intentions. Implications for practitioners are discussed, and suggestions for future research are provided.